Negotiating representation of Islamic values on Korean TV dramas among Indonesian Muslim youth - Rosidi, Imron; Khotimah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article describes one of the effects of globalization on young Muslims in Indonesia. They interact with a variety of cultural products from all corners of the world. Focusing on Indonesia, this article argues that the emergence of globalization has provided opportunities for young Muslims to negotiate Islamic value representations of Korean TV dramas. Using ethnography method, this article selects young Indonesian Muslims who like Korean television drama as informants. The emergence of transnational cultural products was believed to play an important role in the process of 'cultural imperialism' among young people. The information and views presented are not considered to be a ‘healthy’ menu for Muslim youth. In fact, in cultural studies, media imperialism or cultural imperialism is famously contested. By interviewing and observing 42 informants, this article finds that Muslim youth do not receive all the messages from the media passively. During their consumption on Korean television dramas, young Muslims are negotiating their representations. They are capable of selecting values from the television dramas. These Muslim consumers in this context do not just accept all the messages and representations of Korean television dramas. Indonesian Muslim youth have an innate cultural identity and conscious knowledge, which they have obtained from their learning environments such as education and culture. Muslim youth interpret "stories" in drama by relating them to their Islamic values.